Integration of sunflower (Helianthus annuus) residues with a pre-plant herbicide enhances weed suppression in broad bean (Vicia faba) - Alsaadawi,I.S (2011)
Field trial was conducted with the aim of utilizing allelopathic crop residues to reduce the use of synthetic herbicides in broad bean (Vicia faba) fields. Sunflower residue at 600 and 1,400 g m-2 and Treflan (trifluralin) at 50, 75 and 100% of recommended dose were incorporated into the soil alone or in combination with each other. Untreated plots were maintained as a control. Herbicide application in plots amended with sunflower residue had the least total weed count and biomass, which was even better than herbicide used alone. Integration of recommended dose of Treflan with sunflower residue at 1,400 g m-² produced maximum (987.5 g m-2) aboveground biomass of broad bean, which was 74 and 36% higher than control and recommended herbicide dose applied alone, respectively. Combination of herbicide and sunflower residue appeared to better enhance pod number and yield per unit area than herbicide alone. Application of 50% dose of Treflan in plots amended with sunflower residue resulted in similar yield advantage as was noticed with 100% herbicide dose. Chromatographic analysis of residue-infested field soil indicated the presence of several phytotoxic compounds of phenolic nature. Periodic data revealed that maximum suppression in weed density and dry weight synchronized with peak values of phytotoxins observed 4 weeks after incorporation of sunflower residues. Integration of sunflower residues with lower herbicide rates can produce effective weed suppression without compromising yield as a feasible and environmentally sound approach in broad bean fields.